Three Components of Readiness to Change: Communication of Change and Change-Efficacy as Antecendents - Zulkifli Nurul Haqq; Muhammad Natsir (Universitas Muhammadiyah Sidoarjo, 2019)
In order to fulfill the planned change, an organization should seriously take the role of individual perception into consideration, in which the individual plays a pivotal role in the change implementation stage through their act. This study aims to investigate the attitude of readiness to change based on the multidimensional concept, with communication of change and change-efficacy as antecedents. This study involved shariah rural bank, located in East Java, as a research object. Furthermore, a quantitative approach was employed in this study, in which survey as a procedure for collecting data through questionnaires. In addition, PLS-SEM was employed as an analysis of research method. The results exhibit that communication of change contribute to develop of almost all forms attitude of readiness to change and change-efficacy can predict all forms of readiness to change. Finally, this study offers several implications, both theoretically and practically.